P091 Three generations of a family diagnosed with congenital central hypoventilation syndrome: A case series. (9th November 2022) - Pimenta, M; Saddi, V; Thambipillay, G; Teng, A; Blecher, G; Martin, B
Abstract: Introduction: Congenital central hypoventilation syndrome (CCHS) is an autosomal dominant disorder characterized by alveolar hypoventilation and autonomic dysregulation secondary to mutations of the PHOX2B genes.The disorder results in ventilatory impairment characterized by alveolar hypoventilation which worsens in sleep and occurs in individuals with otherwise normal pulmonary mechanics.Diagnosis is based on identification of a pathologic variant in the PHOX2B gene in absence of primary pulmonary, cardiac or neuromuscular disease or a causative brainstem lesion. We present five cases from three generations within the same family with varying degrees of phenotypic expression of the PHOX2B gene mutation. Methods: The identification of CCHS in the index case after birth prompted evaluation of other family members.Genetic testing and counselling were performed for all family members. All family members with a confirmed diagnosis of CCHS underwent a complete assessment. Discussion: We report the unique occurrence of CCHS among five members of a single family in three generations with a varying degree of penetrance and expressivity resulting in diverse clinical manifestations.Early diagnosis and adequate ventilatory management can prevent associated neurologic morbidity and improve long-term outcomes. Providing positive pressure ventilation (PPV) in infants and children with CCHS poses many challenges.Consistency is important as patients with CCHS require lifelong assisted ventilation, at least during sleep, and weaning of ventilation is not advisable.These five cases not only highlight the challenges of managing CCHS, but also the importance of genetic counselling and screening among first-degree relatives and extended family members.